2020
DOI: 10.4103/aja.aja_131_19
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health in Polish elderly men with coronary artery disease: importance, expectations, and reality

Abstract: Deterioration in overall health, hormonal disturbances, and erectile dysfunction (ED) contributes to limitations in sexual activity in the elderly, which is further limited by incorrect beliefs about the hazards of sexual activity in cardiac patients. We aimed to analyze the occurrence of ED in elderly men, their perception of the relevance of good sexual function, and their expectations of physicians. A cross-sectional study encompassed 731 patients with coronary artery disease (CAD) subjected to cardiac reha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Among the included studies, the research conducted by Herut et al [ 41 ] reported the largest sample size with 19,131 participants, while the study by Schwarz et al [ 42 ] had the smallest sample size of 100 participants. The highest quality score based on the JBI checklist belonged to the studies conducted by Rinkūnienė et al [ 23 ], Rusiecki et al [ 43 ], Fafiolu et al [ 44 ], Mulat et al [ 45 ], and Schwarz et al [ 42 ]. The characteristics of the studies included in the systematic review and meta-analysis are provided in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, the research conducted by Herut et al [ 41 ] reported the largest sample size with 19,131 participants, while the study by Schwarz et al [ 42 ] had the smallest sample size of 100 participants. The highest quality score based on the JBI checklist belonged to the studies conducted by Rinkūnienė et al [ 23 ], Rusiecki et al [ 43 ], Fafiolu et al [ 44 ], Mulat et al [ 45 ], and Schwarz et al [ 42 ]. The characteristics of the studies included in the systematic review and meta-analysis are provided in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The standard deviation of the change used in the power calculation was 8.5 points as estimated from review of prior studies. 15 , 16 , 17 , 18 Hence, a 4-point change in score is slightly less than one-half of a standard deviation, or an effect size of 0.47. With the same effect size assessed in females as well, the calculated sample size needed was 50 participants per sex.…”
Section: Methodsmentioning
confidence: 99%